Content management at kapanlagi.com: a study of Indonesian digital media - Reza Safitri; Rachmat Kriyantono; Fitri Avicenna; Nisa Alfira; Azahar Kasim; Normahfuzah Ahmad; Noor Aziah Abdullah (Faculty of Communications Science, Dr. Soetomo University, 2023)
The research aims to explore content management within the digital media landscape of Indonesia, with a specific focus on the strategies employed by Kapanlagi Youniverse (KLY), a renowned digital media platform. Technology is viewed as the paramount factor in implementing communication technology, encompassing the rise of digital media as a transformative force. Employing a descriptive qualitative methodology, this study conducted interviews with eight members of the management team. The findings reveal that KLY utilises three primary strategies: lifestyle entertainment, general news, and sports, which diversify information for readers without limiting the number of operated sites. These findings align with the Long Tail Theory of new media business models, suggesting that expanding reach to previously untapped audiences can lead to success. Effective exploration of the long-tail market requires organisations to address consumer needs at minimal cost. This study presents two key propositions: mergers and acquisitions impact organisational structure and media content, and these changes can be enhanced by applying long tail theory principles.